Penyuluhan Bahaya Cacingan bagi Siswa SD sebagai Upaya Mewujudkan Anak Sehat dan Berprestasi - Ariyanto, Ariyanto; Fatmawati, Tina Yuli (3031-8572, 2024)
Worms are highly infectious disease-causing agents, especially in developing countries. Soil-transmitted helminths (STHs), namely roundworms (Ascaris lumbricoides), hookworms (Necator americanus and Ancylostoma duodenale) and whipworms (Trichuris trichiura), are worms that infect the human intestine and are transmitted through the soil (Lumbantobing et al., 2019). The purpose of this community service is to provide an understanding to students of SDN 068 Jambi City about the dangers of worms and how to prevent them. The sample in this counseling was 20 students, data collection was interviewed with questionnaires before and after education. The analysis used was univariate analysis using the T-Test. The results of the education The average knowledge before counseling about the dangers of worms in elementary school children in state school 068 was 9.3 and the average knowledge after counseling about the dangers of worms in elementary school children in state school 068 was 11.1 and there was an influence of counseling on knowledge of the dangers of worms in elementary school children in state school 068. Therefore, it is recommended for students to always wash their hands before eating, wash their hands with a sponge, wash their hands after defecating, wear footwear outside the home and wear shoes during recess and for the school to provide worm prevention facilities such as providing a place to wash hands, providing hand soap